The utility of the brief ECT cognitive screen (BECS) for early prediction of cognitive adverse effects from ECT: A CARE network study. (January 2022) - Martin, D.M.; Tor, P.C.; Waite, S.; Mohan, T.; Davidson, D.; Sarma, S.; Branjerdporn, G.; Dong, V.; Kwan, E.; Loo, C.K.
Abstract: Although highly effective, electroconvulsive therapy (ECT) often produces cognitive side effects which can be a barrier for patients. Monitoring cognitive side effects during the acute course is therefore recommended to identify patients at increased risk for adverse outcomes. The Brief ECT Cognitive Screen (BECS) is a brief instrument designed to measure emerging cognitive side effects from ECT. The aim of this study was to examine the clinical utility of the BECS for predicting adverse cognitive outcomes in real world clinic settings. The study included data collated from four participating sites in the Clinical Alliance for ECT and Related treatments (CARE) network. The BECS was administered at pre ECT and post 3 or 4 ECT. The primary outcome was a ≥4 point decrease on the Montreal Cognitive Assessment (MoCA) from pretreatment to post ECT. Logistic multiple regression analyses examined the BECS and other relevant clinical and demographic and treatment factors as predictors. The final analysis included 623 patients with diverse indications for ECT including 53.6% with major depression and 33.7% with schizophrenia or schizoaffective disorder. A higher total score on the BECS significantly predicted decline in Total Scores on the MoCA [B = 0.25 (0.08), p = 0.003], though not decline in MoCA Delayed Recall scores (p > 0.1). Other significant predictors included higher pretreatment MoCA Total Scores and female gender for verbal anterograde memory decline. This study confirmed that the BECS has clinical utility for identifying patients with both reduced and increased risk for adverse cognitive outcomes from ECT.